Healthy Movement, Strong Heart: Cardio Exercise as an Intervention for Improving Both Cardiorespiratory Fitness and Cardiovascular Health - Putri Irwanti Sari; Andi Subandi; Meinarisa; Yulia Indah Permata Sari; Rina Oktaria; Indah Mawarti; Yuliana; Riska Amalya Nasution; RTS Netisa Martawinarti (Jurnal Abdimas Kesehatan (JAK), 2026)
Cardiovascular disease remains a major cause of morbidity and mortality in the community. Cardiorespiratory fitness and hemodynamic parameters such as blood pressure, heart rate, and its variability are important indicators of heart health. Cardio exercise as a form of physical intervention has the potential to improve cardiorespiratory fitness and hemodynamic conditions in the community. This Community Service Activity aims to broadcast the effects of exercise on cardiorespiratory fitness and hemodynamic parameters in the community, and to see the extent of changes that occur after regular intervention. The methods used were lectures, interviews, observations and physical examinations (pretest-posttest). Participants totaling 34 people from the local community participated in a 60-minute cardio exercise program. Parameters measured included cardiorespiratory fitness (VO₂max or estimated physical task performance), systolic and diastolic blood pressure, resting heart rate, and heart rate after activity. Results: After the exercise intervention, there was a significant improvement in hemodynamic status. The cardiorespiratory fitness status min-max from 12.93-27.67 ml/kg/min with an average value of 17.11 ml/kg/min. Conclusion: Cardio exercise has been proven to be effective as an intervention to increase cardiorespiratory fitness and improve hemodynamic parameters in the community. Regular cardio exercise programs are recommended as part of a public health strategy for preventing heart disease and improving quality of life.